Korelasi Iman Dan Perbuatan Menurut Yakobus 2:26 Dan Implikasinya Bagi Orang Kristen - Nasrani Winowa’a; Ronaully Marbun (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Christianity is a unique religion, because Christianity is a faith-based religion. Christianity is not a religion with a core of behavior, but the basis of Christianity is Faith. RC Sproul also said that Christianity is Faith because it has the core of faith and because it often talks about the Christian Faith. It is called a faith because there is a knowledge confirmed or believed by its followers. So the quality of Christianity is the quality of being completely in Christ through faith